Exploring Factor Structures Using Variational Autoencoder in Personality Research - Huang, Yufei; Zhang, Jianqiu (Frontiers in Psychology, 2022)
An accurate personality model is crucial to many research fields. Most personality models have been constructed using linear factor analysis (LFA). In this paper, we investigate if an effective deep learning tool for factor extraction: Variational Autoencoder (VAE) can be applied to explore the factor structure of a set of personality variables. To compare VAE with LFA, we applied VAE to an International Personality Item Pool (IPIP) Big 5 dataset and an IPIP HEXACO dataset. We found that LFA tends to break factors into ever smaller yet still significant fractions when the number of assumed latent factors increases, leading to the need to organize personality variables at the factor level and then the facet level. On the other hand, the factor structure returned by VAE is very stable and VAE only adds noise-like factors after significant factors are found as the number of assumed latent factors increases. VAE reported more stable factors by elevating some facets in the HEXACO scale to the factor level. Since this is a data-driven process that exhausts all stable and significant factors that can be found, it is not necessary to further conduct facet level analysis and it’s anticipated that VAE will have broad applications in exploratory factor analysis in personality research.